E-logistics and e-supply chain management applications for evolving business - Graham, Deryn, 1961-; Manikas, Ioannis; Folinas, Dimitris, 1970-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book explores the creation of integrated supply chains, the developments of virtual business, and the processes of re-engineering for business development"--Provided by publisher.
Introduction to e-logistics and e-supply chain management / Deryn Graham -- E-supply chain collaboration and integration: implementation issues and challenges / Sudhanshu Joshi -- Web applications for the outsourcing of logistics services / Dimitris Folinas -- Measuring the impact of tools on the leanness of e-procurement processes / Carina Nicole Leistner -- A hybrid e-auction/negotiation model as a tool for 4PL to improve the transport provider selection process / Eleni Maria Papadopoulou, Athanasios Kelemis -- The use of cloud computing in shipping logistics / Kamalendu Pal, Bill Karakostas -- A web application for supply chain traceability / Ioannis Manikas -- E-enterprise: organisational issues of CRM, SRM, and ERP systems integration / Constantinos J. Stefanou -- Monitoring and warning mechanisms of supply coordination in assembly system under delivery uncertainty / Guo Li, Xiang Zhang, Zhaohua Wang -- The strategic contribution of ERP systems to the formulation of non-financial key performance measures (KPIs) in logistics activities: an exploratory study in northern Greece / Fotios Misopoulos, Sophia P. Asprodini -- The use of RFID technologies for e-enabling logistics supply chains / Zenon Michaelides, Richard Forster -- Cloud computing in supply chain management: an overview / Agorasti Toka ... [et al.] -- A University of Greenwich case study of cloud computing: education as a service / Victor Chang, Gary Wills -- Investigating the effect of e-learning technologies on supply chain activities: the evidence of ELT book market / Dimitrios Terzidis, Fotios Misopoulos -- ERP implementation service supply chain: a modular perspective / Yong Lin ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed March 19, 2013).
Keywords: Business logistics; Electronic commerce; Cloud computing; E-logistics; E-procurement; E-supply chain; Service supply chain; RFID technologies; Web applications; Electronic books